Designing online courts the future of justice is open to all - Loebl, Zbyněk (Kluwer Law International B.V., 2019)
Designing Online Courts' provides a template for how online courts should be designed with a focus on end-users of the justice system. The newest phenomenon in the field of online dispute resolution (ODR) is the emergence of online courts. New online courts are radically different from traditional courts and this will continue. Holding great promise for end-users of the justice system, online courts can expand access to remedies, improve efficiency and lead to greater fairness and even cost savings. Nonetheless, there is a danger that the rush to digitization will compromise due process or the need for careful re-designing of judicial procedures. This book, focusing on ethical issues and key implementation topics, is the first to provide a comprehensive template for how online courts should be designed. It recognizes the need to adapt dispute resolution to a new environment in which constraints of space and time are lifted as cross-border transactions and instant communication become commonplace.